2002
DOI: 10.2138/am-2002-11-1221
|View full text |Cite
|
Sign up to set email alerts
|

The influence of bulk composition on the diffusivity of carbon dioxide in Na aluminosilicate melts

Abstract: The bulk diffusivity of dissolved carbon dioxide (CO 2 and CO 3 2-) in NaAlSi 3 O 8 + nNa 2 O (n = 0-6.87 wt%) and in NaAlSi 3 O 8 + nH 2 O (n = 0-2 wt%) melts was investigated at 1523 K and 0.5 GPa using the diffusion couple technique. CO 2 contents of the starting glass pairs varied between 0 and 0.2 wt%. Symmetrical concentration-distance profiles of bulk CO 2 were determined by infrared spectroscopy. An error function was fitted to the profiles to obtain apparent chemical diffusion coefficients of bulk CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 26 publications
8
32
0
Order By: Relevance
“…Sierralta et al (2002) have recently demonstrated that in contrast to Pt capsule material, CO 2 -bearing glass cylinders synthesized in Au80Pd20 capsules show no CO 2 loss and zoning of CO 2 concentration towards the capsule walls. Silver oxalate (Ag 2 C 2 O 4 ) equivalent to 0.2 wt% CO 2 was used as the CO 2 source.…”
Section: Synthesis Of Glass Cylinders For Diffusion Couple Experimentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sierralta et al (2002) have recently demonstrated that in contrast to Pt capsule material, CO 2 -bearing glass cylinders synthesized in Au80Pd20 capsules show no CO 2 loss and zoning of CO 2 concentration towards the capsule walls. Silver oxalate (Ag 2 C 2 O 4 ) equivalent to 0.2 wt% CO 2 was used as the CO 2 source.…”
Section: Synthesis Of Glass Cylinders For Diffusion Couple Experimentsmentioning
confidence: 99%
“…Silver oxalate (Ag 2 C 2 O 4 ) equivalent to 0.2 wt% CO 2 was used as the CO 2 source. Details for capsule preparation are given in Sierralta et al (2002) and Nowak et al (2003). The syntheses were run at 1623 K and 500 MPa in the IHPV at intrinsic oxidising conditions equivalent to the MnOMn 3 O 4 solid oxygen buffer (logfO 2 ϭ QFM ϩ 4) (Berndt et al, 2002).…”
Section: Synthesis Of Glass Cylinders For Diffusion Couple Experimentsmentioning
confidence: 99%
See 3 more Smart Citations